2018
DOI: 10.4172/2155-9546.1000548
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas Infections in African Sharptooth Catfish

Abstract: The aim of this study was to investigate the dominant species of Aeromonas in naturally infected African Sharptooth catfish, Clarias gariepinus, in Qena, Egypt and the distribution of two virulence genes among the isolates to assess their pathogenicity. Twenty-five isolates of Aeromonas were recovered from infected fish showing signs of septicemia. Restriction-fragment-length-polymorphism (RFLP) analysis of the 16S-rDNA amplified products demonstrated that the specie isolated were Aeromonas hydrophila (56%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(46 reference statements)
2
11
0
1
Order By: Relevance
“…This study also showed that Aeromonas have at least four virulence genes. Similar results have been reported for aer/haem and flaA [ 30 , 62 ]. Aerolysin is a hemolytic extracellular product coded by the aerolysin gene and plays a significant role in the pathogenicity of Aeromonas spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study also showed that Aeromonas have at least four virulence genes. Similar results have been reported for aer/haem and flaA [ 30 , 62 ]. Aerolysin is a hemolytic extracellular product coded by the aerolysin gene and plays a significant role in the pathogenicity of Aeromonas spp.…”
Section: Discussionsupporting
confidence: 90%
“…The previous study has also identified Aeromonas spp. from catfish ( Clarias gariepinus ) in Egypt using genotypic analysis, these bacteria consisted of A. hydrophila (56%) and A. veronii (44%) [ 62 ], A. hydrophila (50.4%), and A. caviae (5.6%) according to phenotypic analysis [ 63 ]. Other research on catfish in Uganda discovered A. hydrophila (33%) and A. sobria (33%) through genotypic analysis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disease is caused by members of the genus Aeromonas, such as Aeromonas hydrophila, A. veronii, A. dhakensis, A. jandaei, A. sobria and A. caviae [7][8][9][10][11][12]. The disease was described as having two forms, the acute hemorrhagic septicemia and the chronic ulcerative syndrome [13][14][15]. The genus Aeromonas plays an important role in diseases of aquaculture, with Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Bakteri ini menyebabkan penyakit MAS dalam spektrum yang luas pada ikan maupun biota air lainnya (Zhou et al, 2011;Qi et al, 2016;Raji et al, 2019). Gejala yang ditimbulkan pada lele yang terinfeksi A. hydrophila antara lain hemoragik yang tersebar di seluruh bagian tubuh, pengelupasan dan congesti pada sirip ekor, ulcer, hemoragik dan kongesti pada hati, ginjal,dan limpa, serta abdominal cavity (Emeish et al, 2018).…”
Section: Pendahuluanunclassified